Genome and Transcriptome Adaptation Accompanying Emergence of the Definitive Type 2 Host-Restricted Salmonella enterica Serovar Typhimurium Pathovar - Robert A. Kingsley (American Society for Microbiology, 2013)
ABSTRACT Salmonella enterica serovar Typhimurium definitive type 2 (DT2) is host restricted to Columba livia (rock or feral pigeon) but is also closely related to S. Typhimurium isolates that circulate in livestock and cause a zoonosis characterized by gastroenteritis in humans. DT2 isolates formed a distinct phylogenetic cluster within S. Typhimurium based on whole-genome-sequence polymorphisms. Comparative genome analysis of DT2 94-213 and S. Typhimurium SL1344, DT104, and D23580 identified few differences in gene content with the exception of variations within prophages. However, DT2 94-213 harbored 22 pseudogenes that were intact in other closely related S. Typhimurium strains. We report a novel in silico approach to identify single amino acid substitutions in proteins that have a high probability of a functional impact. One polymorphism identified using this method, a single-residue deletion in the Tar protein, abrogated chemotaxis to aspartate in vitro. DT2 94-213 also exhibited an altered transcriptional profile in response to culture at 42°C compared to that of SL1344. Such differentially regulated genes included a number involved in flagellum biosynthesis and motility. IMPORTANCE Whereas Salmonella enterica serovar Typhimurium can infect a wide range of animal species, some variants within this serovar exhibit a more limited host range and altered disease potential. Phylogenetic analysis based on whole-genome sequences can identify lineages associated with specific virulence traits, including host adaptation. This study represents one of the first to link pathogen-specific genetic signatures, including coding capacity, genome degradation, and transcriptional responses to host adaptation within a Salmonella serovar. We performed comparative genome analysis of reference and pigeon-adapted definitive type 2 (DT2) S. Typhimurium isolates alongside phenotypic and transcriptome analyses, to identify genetic signatures linked to host adaptation within the DT2 lineage.